Development of a Non-Revenue Water Management System for Mpoma Village in Mukono District - Modecai Stanly Muhanguzi (Uganda Christian University, 2024)
The development of a Non-Revenue Water (NRW) Management System for Mpoma Village in Mukono District, Uganda, represents an innovative strategy for addressing the critical problem of water leakage within water distribution networks. This project concentrated on deploying innovative sensor-based technologies for the real-time monitoring of water distribution with the goal of identifying and addressing illegal water connections, a key factor in NRW. Leveraging EPANET for hydraulic modelling and Python for data analysis, the study introduced a comprehensive NRW management framework. This framework includes real-time data analysis, predictive modelling, and an effective anomaly detection system for efficiently identifying potential leakages and unauthorized water use. Demonstrating significant potential to reduce NRW in Mpoma Village, the project also established a model that can be replicated in other regions facing similar challenges. The findings highlight the critical role of integrating technology with community engagement and policy frameworks for the sustainable management of water resources and fair distribution. With thorough data collection, analysis, and the application of engineering principles, this research makes a substantial contribution to global NRW reduction efforts, showcasing a mix of technical innovation and practical solutions.